Ukuran Perusahaan, Profitabilitas, Leverage, dan Pengungkapan Tanggung Jawab Perusahaan Bank di Indonesia - Machmuddah, Zaky; Sumaryati, Anna; Komara, Acep (Jurnal Kajian Akuntansi, 2024)
This study aims to empirically test the influence of financial performance as proxied by return on assets and leverage on corporate social responsibility (CSR) disclosure and is strengthened by company size. This research is important because the object of this research is banking companies which have a crucial role in considering environmental issues in providing credit. Even though banking companies are notdirectly involved in environmental damage issues. The object of this study is banking companies listed on the Indonesia Stock Exchange in 2017-2022. The sample in this study was 21 banking companies selected using a purposive sampling technique and the sample years of these companies were notconsecutive so that 115 observational data were obtained. The analysis technique in this research uses WarpPLS version 7.0. The results of this research show that leverage has a positive influence on corporate social responsibility and company size plays a role in strengthening this influence. However,profitability does not have a positive influence on corporate social responsibility, while company size strengthens this influence. The implication of this research is the importance of corporate social responsibility disclosure which is supported by leverage and company size for the survival of the company.